Contribuição ao conhecimento de neogerris visendus, Drake e Haris, 1934. (hemiptera: gerridae). - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1994)
Neogerris visendus, the object of study in this paper, is one of the representatives of the family Gerridae. These are characterized by living on the water surface. Adult males and females were captured in the natural habitat and brought to the laboratory, where they were kept at an average temperature of 27°C and relative humidity of 80%. The pairs were kept in 1Ox13x25cm tanks with 5cm of water. Under these conditions, the following data were obtained: eggs, incubation period of 7 days on average; nymphs: first instar ecdysis in an average period of 6,2 days, second instar in an average period of 5,6 days, third instar in 5,9 days on average, fourth instar in 5,8 days on average and fifth instar in 6 days on average. The total cycle from egg to adult is around 36 days, ranging from 29 to 46 days. Copulation of these specimens is by riding and lasts an average of 20 minutes. Due to the short life cycle of this species and the easy adaptation to laboratory conditions, it is possible to develop studies on its biology, as well as studies on cytogenetics, histology, etc.
Contribution to the knowledge of neogerris visendus, Drake and Haris, 1934. (hemiptera: gerridae).
Keywords: Neogerris visendus; Gerridae; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA